2021
DOI: 10.1016/j.jopan.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient State Index Monitoring on the Recovery Characteristics in Morbidly Obese Patients: Comparison of Inhalation Anesthesia and Total Intravenous Anesthesia

Abstract: Obese patients have a significantly higher risk of adverse effects associated with general anesthesia. The purpose of this study was to evaluate the effects of Patient State Index (PSI) monitoring on recovery from anesthesia and the incidence of any postoperative complications among patients undergoing bariatric surgery with total intravenous anesthesia (TIVA) and inhalational anesthesia. Design: This prospective, double-blind, and randomized controlled trial was conducted between February 2017 and August 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The majority of studies retrieved concerned the cardiovascular (n = 14) [9][10][11][12][13][14][15][16][17][18][19][20][21][22], respiratory (n = 7) [23][24][25][26][27][28][29], and neurological (n = 9) [30][31][32][33][34][35][36][37] systems. Two pertained to point-of-care testing [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies retrieved concerned the cardiovascular (n = 14) [9][10][11][12][13][14][15][16][17][18][19][20][21][22], respiratory (n = 7) [23][24][25][26][27][28][29], and neurological (n = 9) [30][31][32][33][34][35][36][37] systems. Two pertained to point-of-care testing [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Along with that, surgical procedures in such patients are also increasing. Obese patients are at a higher risk to anesthesia related complications when compared to patients in the normal weight range (15). Obese patients are more prone to diseases such as Postoperative atelectasis and sleep apnea syndrome when compared to their normal counterpart (16).…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported on intraoperative vital signs. Four studies reported no statistically significant differences in the heart rates in a total of 336 patients [ 28 , 29 , 34 , 35 ]. One study reported that in all 100 patients studied, despite having comparable heart rates at baseline, the TIVA group recorded significantly lower heart rates from induction to discharge from PACU [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of the five studies (396 patients) that reported PONV, three found no difference in the incidence of PONV (176 patients) [ 26 , 30 , 36 ], and two studies (220 patients) reported that patients who received TIVA had a lower incidence of these effects [ 31 , 35 ].…”
Section: Reviewmentioning
confidence: 99%